Productive and reproductive performance of local cows under farmer’s management in central Tigray, Ethiopia. - Abrha, B. H.; Niraj , K.; Berihu , G.; Kiros , A.; Gebregiorgis , A. G. (Nigerian Journal of Animal Science, 2023)
The study was conducted on 408 indigenous cows maintained under farmer’s management in eight districts of central Tigray, Ethiopia. A total of 208 small-scale dairy farm owners were randomly selected and interviewed with structured questionnaire to obtain information on the productive and reproductive performance of indigenous cows. The results of the study showed that the mean age at first calving (AFC) was 43.3 ±2.7 months, number of services per conception (NSC) was 2.7±0.5, days open (DO) was 201.47±61.21 days, calving interval (CI) was 468.33±71.42 days, lactation length (LL) was 206.17±32.33 days, lactation milk yield (LMY) was 414.65±53.69 litres for indigenous cows. The estimated value for productive and reproductive traits had higher than normal range in indigenous cows. This calls for a planned technical and institutional intervention for improved support services for appropriate breeding programs, improved cows and adequate veterinary health services.